Mekanisme Pertahanan Ego Tokoh Zenchi Naigu Dalam Cerpen Hana Karya Akutagawa Ryunosuke - Aditya, I Wayan Deva; Antartika, I Kadek; Sadyana , I Wayan (Jurnal Penelitian Mahasiswa Indonesia, 2024)
This research aims to describe the forms of ego defense mechanisms from the character named Zenchi Naigu in the short story "Hana" by Akutagawa Ryunosuke, in dealing with his anxiety that caused by physical abnormality (a long nose). The process of collecting data was using a note-taking method, then analyzed with descriptive qualitative. The theory employed is Sigmund Freud's psychoanalysis theory with a literary psychology approach. The classification of ego defense mechanisms used refers to the classification proposed by Albertine Minderop. The results showed that there are six forms of ego defense mechanisms by the character Zenchi Naigu in order to cope with his anxiety, such as rationalization, repression, sublimation, reaction formation, stereotype, and displacement. The part of rationalization is the most dominant ego defense mechanism used by Zenchi Naigu to suppress his anxiety. The ego attempts to justify the id’s desire to have a short nose by providing rational reasons that can be accepted by his superego through the rationalization. The ego defense mechanisms used by Zenchi Naigu to prevent the situations that can cause anxiety, discomfort, or internal conflicts resulting from id desires that cannot be accepted by the superego, as they contradict the values upheld from the character Zenchi Naigu.